No effect of AR polyG polymorphism on spinal and bulbar muscular atrophy phenotype. (June 2016) - Bertolin, C.; Querin, G.; Da Re, E.; Sagnelli, A.; Bello, L.; Cao, M.; Muscas, M.; Pennuto, M.; Ermani, M.; Pegoraro, E.; Mariotti, C.; Gellera, C.; et al.
Abstract : Background and purpose: Disease severity varies considerably among patients with Spinal and Bulbar Muscular Atrophy (SBMA). Our aim was to investigate the role of androgen receptor ( AR ) polymorphic repeats in SBMA phenotype. Methods: We analyzed the length of AR polyQ and polyG tracts in 159 SBMA patients. Results: No relationship between polyG size or polyG/polyQ haplotypes and clinical phenotype was found. An independent negative correlation between polyQ‐length and onset of weakness was confirmed ( P < 0.001). Conclusions: The negative results of our study prompt to continue the search for potential disease modifiers in SBMA outside the AR gene.